The time of repetition in the violin music of H. I. F. von Biber and C. A. Lonati (ACME, 2024)
The principle of repetition plays a fundamental role in every form of musical expression and represent one of the most common and effective compositional expedients. Oscillating between stasis and continuous movement, the iterative processes and modular sequences decisively influence the perception of space and time and challenge the listener’s expectations, creating labyrinthine and obsessive architectures, and hypnotic modules, which generate an emotional impact.The essay examines in an interdisciplinary perspective the systematic use of repetition in the violin music of two of the greatest violinist-composers active in the late seventeenth century in the area straddling the Alps: Heinrich Ignaz Franz von Biber (1644-1704) and Carlo Ambrogio Lonati (c. 1645-post1701). The two composers, employing similar or different approaches, exploited repetition both to challenge the performer’s executive expertise and to consolidate, disintegrate or remodulate the formal and temporal architecture of the pieces, producing ‘bizarre’ and ingenious dispositions of the episodes. The analysis of some relevant examples and the comparison between the two composers will permit to highlight a range of compositional attitudes and expedients and will offer new interpretation keys, also applicable to other musical repertoires and areas of knowledge.
Keywords: Musical repetition; modularity; bizzarria; instrumental perfidia; Seventeenth-century Violin virtuosity